Character Values in Riko the Series Episode "Early Prayers of Time" for Elementary School Students - Intan Puspita Nurdiani; Syarip Hidayat; Pidi Mohamad Setiadi (Journal of Future Education, 2023)
The development of the times makes it easier for children to access anything via the internet so it is not uncommon for children to imitate what they watch and affect the character they have. The film Riko The Series is one of the interesting animated films. For this reason, the purpose of this article is to analyze what character values are in the film Riko The Series which can be a medium for conveying moral values and character to elementary school-age children. This research uses a descriptive qualitative approach with the literature study method. The research results showed that the film Riko The Series contained various character values and produced 20 data in the episode studied by the author. The character values that emerged were religious character values found as many as 10 data, 1 data creative, 4 data curiosity, 2 data respecting achievement, 2 data responsibility, and 1 data discipline. Religious characters are characters that often appear in the animated film Riko The Series. This also shows that the animated film Riko The Series can be a medium for educational viewing for students and can also be used as a medium of learning that is rich in religious values and can be applied in lower grade elementary schools, especially in learning Islamic religious education.